Sengketa Pemilukada; Menegakkan Keadilan dalam Hasil dan Proses (Analisis Putusan MK Nomor 28/PHPU.D-VIII/2010 tentang Pemilukada Kabupaten Gresik) - Kurniawan, Wishnu (Mahkamah Konstitusi Republik Indonesia, 2011)
Democracy process of the Republic of Indonesia has changed over the collapse of the regime’s Suharto. Submission of opinion/ voting rights before the election form through representation in the Legislative votes, while the order of the reform party of Indonesia’s democracy changed the form with a direct election of the aspirations of the community through direct election of the executive (President, Governor, and Mayor / Regent)Democratic party face has changed get a hidrance and obstacle, the hidrance and thats obstacle shapes as money politic, black campaign, veiled campaign, inflate a number of vote, etc. But to canceled that fraud, indonesian civilans & the participants/incumbent has a place to uphold the justice throught the Constitutional Court..Based on the result data processing and analysis carried out performed within this scientific can be concluced that The Constitutional Court actually has authority to receive, examine, prosecute, decide land disputes election result. Constitution Court decision especially about the election result dispute regional head (Regent and Vice Regent) by the Conctitution Court election result with number 28/PHPU.D-VIII/2010 about Perselisihan Hasil Pemilihan Umum Kepala Daerah dan Wakil Kepala Daerah Kabupaten Gresik, Provinsi Jawa Timur Tahun 2010 can be operate well and has gained a place at Gresik Regency civilians.